2009 IEEE International Symposium on Biomedical Imaging: From Nano to Macro 2009
DOI: 10.1109/isbi.2009.5193139
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variability of organs via principal factor analysis from the construction of an abdominal probabilistic atlas

Abstract: Extensive recent work has taken place on the construction of probabilistic atlases of anatomical organ. We propose a probabilistic atlas of ten major abdominal organs which retains structural variability by using a size-preserving affine registration, and normalizes the physical organ locations to an anatomical landmark. Restricting the degrees of freedom in the transformation, the bias from the reference data is minimized, in terms of organ shape, size and position. Additionally, we present a scheme for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…According to the original works presented by Reyes et al (2009, 2010), the analysis of deformation fields showed correlation with existing anatomical landmarks and known anatomical deformations of abdominal organs. The subdivision of organs into anatomically significant components defined by clusters may be of great utility in the study and analysis of the anatomical variability of organs and inter-organs relations, an important research tool for diagnosis, modeling, and soft tissue intervention.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…According to the original works presented by Reyes et al (2009, 2010), the analysis of deformation fields showed correlation with existing anatomical landmarks and known anatomical deformations of abdominal organs. The subdivision of organs into anatomically significant components defined by clusters may be of great utility in the study and analysis of the anatomical variability of organs and inter-organs relations, an important research tool for diagnosis, modeling, and soft tissue intervention.…”
Section: Resultsmentioning
confidence: 98%
“…In this section we introduce a new landmark clustering approach that allows us to automatically define the division of landmarks into separate clusters at each resolution. The clustering process was initially inspired by the work presented by Roy et al (2006), which was originally conducted for vector field segmentation of moving objects in 2D videos, and extended to 3D objects by Reyes et al (2009) to study the anatomical variability of single organs via principal factor analysis. Here we propose a more general approach based on the agglomerative hierarchical clustering method presented by Ward (1963).…”
Section: Automatic Hierarchical Decompositionmentioning
confidence: 99%
“…Similar efforts have been applied across abdominal tissues (Reyes et al, 2009), multiple brain regions (Mazziotta et al, 2001;Habas et al, 2010;Pauli et al, 2018), and the lung (Hame et al, 2014;Yang et al, 2017). However, the examination of different measures of variability for current human atlas efforts provides an opportunity to relate morphological and molecular variation.…”
Section: Figure 2 Hierarchical Organization Of Coordinate Systemsmentioning
confidence: 99%
“…It is a difficult task considering a high degree of variability in medical image quality to include penetration and positioning [ 2 ]. To overcome such variety, typical approaches in medical image segmentation develop solutions that are specific to the medical imaging modality, body part, or disease being studied [ 3 ]. This results in the limited direct use of segmentation models commonly trained on natural images for medical image segmentation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%